The impact of climate change on tourism in Germany, the UK and Ireland: A simulation study - Jacqueline M. Hamilton; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2006)
We downscale the results of a global tourism simulation model at a national resolution to a regional resolution. We use this to investigate the impact of climate change on the regions of Germany, Ireland and the UK. Because of climate change, tourists from all three countries would spend more holidays in the home country. In all three countries, climate change would first reduce the number of international arrivals - as Western European international tourist demand falls - but later increase numbers - as tourism demand from increasingly rich tropical countries grows. In Ireland and the UK, the regional pattern of demand shifts is similar to the international one: Tourism shifts north. In Germany, the opposite pattern is observed as the continental interior warms faster than the coast: Tourism shifts south.
Keywords: 330; International tourism; domestic tourism; climate change; regional impacts